HOW TO STRENGTHENING OR WEAKENING THE PROCEDURES OF CORPORATE GOVERNANCE: AN ARTIFICIAL INTELLIGENCE PERSPECTIVE - Raghad Ahmed (Transpublika Publisher, 2024)
This research aims to examine the impact of artificial intelligence (AI) on corporate governance practices in non-financial enterprises in Qatar. It explores how AI can either strengthen or weaken these practices and provides suggestions for integrating AI into corporate governance. The study utilizes case studies, actual data, and existing literature, along with a non-interview-based methodology, to analyze the connection between corporate governance and AI. Through synthesis and comparison, this research offers a comprehensive examination of the subject. It acknowledges the unique challenges and opportunities faced by non-financial organizations in Qatar when implementing AI for corporate governance. The insights provided in this research are relevant not only to similar businesses in other locations but also highlight the importance of incorporating AI into corporate governance procedures. The findings emphasize the need for businesses to invest in AI technology and for legislators to establish supportive laws for AI's application in corporate governance. This study stands out from previous research by focusing on the relationship between AI and corporate governance and highlighting the role of AI in enhancing business performance. The conclusions drawn from this study are valuable for regulators, legislators, and businesses seeking to leverage AI for improved corporate governance.